Radio frequency combination for TCP/IP suite protocol improvement in 4G mobile internet networks - Gani, Abdullah; Li, X.; Yang, L.; Zakaria, O. (2008)
In this paper, we present our new proposed protocol to enhance the TCP/IP versatility as the main protocol for wireless data transmission. TCP/IP has shown its superiority in the selection of protocol for establishing wired networks. Unfortunately, its superiority cannot be extended to wireless networks. However, we believe that the integration of several types of networks would take place. The 4th Generation (4G) wireless mobile internet networks will merge the current existing cellular networks (i.e., CDMA2000, WCDMA and TDSCDMA) and Wi-Fi networks (i.e., Wireless LAN) with the fixed internet to support wireless mobile internet. This integration would provide the same quality of service as fixed internet. Each of the networks has their own specified protocols, disparity frequency, and maximum data speed and cost characteristics. TCP/IP suite protocols were successful in web application of fixed internet, but exhibit limitation to work on the combined networks. Two research directions are available, which are replacement and improvement. Microsoft has issued a new protocol suite for replacement. In this paper, we propose a new protocol to improve TCP/IP suite protocols. This new protocol addresses the limitation of TCP/IP suite so that it can work on both cellular network and Wi-Fi network simultaneously; sending data requests through cellular network and getting reply from Wi-Fi network. Ns2 Java version (Java Network Simulator) was chosen to simulate the new protocol because of its feasibility. In this paper, we present the results and discussion of our simulation.